Impacts of Teak Defoliator (Hyblaea puera) in Carbon Accumulation in Teak (Tectona grandis) Plantation Forest - Madan Raj Bhandari; Subodh Bhattarai (Pandawa Institute, 2022)
Among the insects attacking teak well-known pests of the teak tree (Tectona grandis) i.e., Hyblaea puera (Lepidoptera: Hyblaeidae), popularly known as the teak defoliator is the most widespread and serious pest causing a loss in increment volume of plants. Having a high economic timber value, Tectona grandis has also played an important role in storing carbon. Hence, the present investigation has attempted to study the impacts of teaks defoliator Hyblaea puera on carbon stocks accumulation and overall growth in plantation forests and make acomparison with healthy teak plantation forests without the impacts of teak defoliator. Remaining all other factors constant, the study conducted on tropical regions of eastern Nepal has shown an 18% increase in carbon stocks in 2 years in the teak defoliator infected patch whereas it’s 38% in the healthy patch. Similarly, a highly positive correlation was found between diameter and height in a healthy patch in both the measurement i.e., 0.88 and 0.89. Whereas there is less positive correlation i.e.,0.64 and 0.69 in the infected patch.The mean height increment of the healthy plot was 1.1, while it was 0.5 in the case of the infected plot. Furthermore, the Mean DBH Increment of the Healthy plot was 2.1; however, it was 1.0 in the case of the infected plot. To sum up, this study at tropical regions has presented the impacts of teak defoliator (Hyblaea puera) on growth(height and diameter) and carbon accumulation on Teak plantation area.